The effects of Expressing Writing on Palliative Care healthcare professionals: a qualitative study - Cosentino, Chiara; Baccarini, Elena; Melotto, Martina; Meglioraldi, Riccardo; D'Antimi, Silvia; Semeraro, Valentina; Cervantes Camacho, Victoria; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Expressive Writing (EW) is a useful tool for taking care of the person globally, and literature shows that self-care and self-awareness improve the coping skills of health professionals, positively increasing personal and professional satisfaction and reducing the negative aspects related to the profession, such as burnout. The objective of the research is to analyze the writings produced by healthcare professionals belonging to palliative care in a previous quantitative study to identify any changes between two sessions. Methods: It is a longitudinal qualitative research with an interpretative phenomenological methodology of analysis of documents written by professionals. The study included 50 expressive writings: 25 at Time 0 (T0) and 25 at Time 1 (T1). The analysis sample is composed of 25 professionals. All participants completed an Expressive Writing protocol homogeneous in procedure, mandate, and timing. Results: The study revealed a variation in contents from T0 to T1 highlighting both professional and intimate growth of the professionals. The practitioner appears more aware of working together to achieve a goal. Writing evolve as more spontaneous. Attention is focused on the relationship with the patient as an engine of personal and professional growth. The satisfaction is linked to the management of a complex case in its entirety. Conclusions: The investigated instrument resulted in a beneficial change in the healthcare professionals involved. Writing helps to find strategies to take care of the other, improves communication, favors the sharing of experience with the other, increasing the awareness of limitations and strengths.